2012
DOI: 10.5251/abjna.2012.3.1.25.30
|View full text |Cite
|
Sign up to set email alerts
|

Effect of four different tillage practices on maize performance under rainfed conditions

Abstract: An experiment was conducted to determine the effect of tillage practices on moisture retention and maize performance under rainfed conditions in Swaziland. The five treatments were based on structure of seedbed and seed planting method. They were ; zero tillage where jab planter was used to directly seed (JAB), tractor drawn planter to directly seed without ploughing (TDSS), tractor drawn cultivator to loosen soil followed by planting with tractor planter (TDRDS), planting basics made by using hand hoe (PLB) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 18 publications
8
17
0
Order By: Relevance
“…Deep tillage was seen an improved practice regarding plant height and but flat sowing remained inefficient to improve plant height as compared to ridge and bed sowing. Borghei et al [18] and Wasaya et al [19] who concluded that sub-soiling up to 50 -55 cm caused the highest average plant height while our results were contradictive to Najafinezhad et al [20] who concluded that conventional tillage (CT) and reduced tillage (RT) plots exhibited highest plant height whereas stem diameter remained in effective by different tillage operations and sowing methods which was found in line with Aikins et al [21], who concluded that maize stem girth was non-significant under different tillage practices. Moreover, deep tillage and ridge sowing improved leaf area, leaf area index and crop growth rate of maize which found in accordance with the results reported by Rasheed et al [22] and Balasubramaniyan et al [23] who found that maize crop sown on ridges gave considerably higher leaf area index (5.22) and further elucidated that planting methods influenced leaf area index positively and crop growth rate of maize significantly.…”
Section: Discussionsupporting
confidence: 69%
“…Deep tillage was seen an improved practice regarding plant height and but flat sowing remained inefficient to improve plant height as compared to ridge and bed sowing. Borghei et al [18] and Wasaya et al [19] who concluded that sub-soiling up to 50 -55 cm caused the highest average plant height while our results were contradictive to Najafinezhad et al [20] who concluded that conventional tillage (CT) and reduced tillage (RT) plots exhibited highest plant height whereas stem diameter remained in effective by different tillage operations and sowing methods which was found in line with Aikins et al [21], who concluded that maize stem girth was non-significant under different tillage practices. Moreover, deep tillage and ridge sowing improved leaf area, leaf area index and crop growth rate of maize which found in accordance with the results reported by Rasheed et al [22] and Balasubramaniyan et al [23] who found that maize crop sown on ridges gave considerably higher leaf area index (5.22) and further elucidated that planting methods influenced leaf area index positively and crop growth rate of maize significantly.…”
Section: Discussionsupporting
confidence: 69%
“…Ahmad et al (2005) also concluded that the application of 120 kg N haG 1 increased maize plant height. Similarly, Hammad et al (2011) also reported that there was more vegetative as well as reproductive growth with increase in the amount of N. In line with our current findings, Aikins et al (2012) also found no significant effect of tillage on plant height and in another similar study, Al-Ghrerie (1988) also reported that zero tillage and conventional tillage showed no significant effect on plant height of maize.…”
Section: Plant Heightsupporting
confidence: 82%
“…Similar results were observed in a study done in Turkey where plants under conventional tillage were higher than those under no till [24]. In a study done in Ghana there was no significance in difference for mean height between different tillage treatments, even though the shorted plant was found in the no tillage treatment [25]. The great plant height under conventional tillage may be attributed to better soil aeration and more uniform distribution of nutrients in soil profile [26].…”
Section: Treatmentsupporting
confidence: 75%